The Concept of Hijrah in the Al-Qur’an: Contextualization in the Millennial Era in the Ma'na-Cūm-Maghza Approach - Nur Habib Musthofa (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
In this millennial era, emigration has become a very popular religious issue. The problem with the term hijrah itself is not only misunderstood, but the term hijrah in this melennial era is also misused by several groups. This is because the term hijrah nowadays, apart from experiencing reconstruction of meaning, has also undergone commodification in terms of application. In this problem, researchers try to examine verses that explain the hijrah contained in the Qur'an using the Ma'nā-cum-Maghzā approach theory. This is because this method combines classical Islamic scholarship and modern hermeneutics which is relatively new in the academic realm. In this research, researchers will look for the relevance of the meaning of hijrah and its understanding in the present. Researchers concluded that the migration itself was carried out long before the time of Muhammad's prophethood. However, the term hijrah itself became popular among Muslims during the first migration of the Prophet Muhammad, namely from the city of Mecca to the city of Medina. The emigration of the Prophet Muhammad at that time was due to saving himself and the people from interference and pressure from infidels who rejected the teachings brought by the Prophet Muhammad at that time. During the prophetic period, researchers discovered several significance of the hijrah, namely; At first, the command to emigrate aims to save oneself, religion, and even the people from interference from infidels. Second, the command to emigrate to abandon sinful acts. Third, the command to emigrate to disseminate the teachings ordered by Allah SWT. Fourth, the command to help people who emigrate. Fifth, the value of hijrah contains a serious message. In the current era, researchers explain that the significance and relevance of hijrah in the current context (Maghza Al-Ayah) is: First, to improve oneself for the better, by abandoning sins or actions that are prohibited by religion. Second, to help each other in good things. Third, be serious about doing a good deed.